(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
The purpose of this paper is to establish some new criteria for the oscillation of the second-order nonlinear noncanonical difference equations of the form ∆ (a (n) ∆x (n)) + q(n)x^β (g(n)) = 0, n ≥ n_0 under the assumption ^∞_s=n 1a(s)< ∞. Corresponding difference equations of both retarded and advanced type are studied. A particular example of Euler type equation is provided in order to illustrate the significance of our main results.